Comparison of the effect of green, white and black tea on Streptococcus thermophilus and Lactobacillus spp. in yogurt during refrigerated storage - Muniandy, P.; Shori, A.B.; Baba, A.S. (Taylor & Francis Open, 2017)
This study investigated the effects of green, white and black tea (Camellia sinensis) on lactic acid production and the viability of Streptococcus thermophilus and Lactobacillus spp. in yogurt during 3 weeks of refrigerated storage. Three types of tea water extracts were added into a milk-starter culture mixture and incubated at 42 °C until the pH was reduced to 4.5. All yogurts were then refrigerated (4 °C) for up to 21 days and samples were analyzed for pH, titratable acid and viable counts of yogurt bacteria. Higher pH values (p < 0.05) were shown in tea yogurts than plain yogurt (PY). Green tea yogurt (GTY) showed the highest pH followed by black tea yogurt (BTY) and white tea yogurt (WTY), respectively for the overall storage period. However, higher acid production was observed in all tea yogurts (0.78–0.99% lactic acid equivalent; LAE) than plain yogurt (0.70–0.91% LAE). Inclusion of three types of tea extracts did not affect significantly (p > 0.05) the viability of Lactobacillus spp. and S. thermophilus compared to PY during storage. All the three types of tea yogurt maintained a high level of S. thermophilus and Lactobacilllus spp. counts through refrigerated storage and this can ensure health benefits to be delivered to consumers on daily consumption.